Regional organisational audit of district departments of public health. Issue 2 (June 1994) - Alpin, V C; Bhan, A; Bennett, J; Bergmann, M
Abstract : Organisational audit of public health in the United Kingdom is rare. To provide a framework for a structured organisational audit in district public health departments in one region organisational factors contributing to efficient, high quality work were identified and compared between districts, enabling each department to identify its organisational strengths and weaknesses. A draft list of organisational factors, based on the King's Fund organisational audit programme, were rated by 52 public health physicians and trainees in 12 district public health departments in South East Thames region for their importance on a scale of 0 (not relevant) to 5 (vital). Factors with average ratings of > 4, judged to be "vital" and proxies for standards, were then used to compare each district's actual performance, as reported by its director of public health in a self reported questionnaire. In all, 37 responses were received to the rating questionnaire (response rate 71%) and 12 responses to the directors' questionnaire. Of the 54 factors identified as vital factors, 20(37%) were achieved in all 12 districts and 16(30%) in all but one district; 18 were not being achieved by two (33%) districts or more. Overall, vital factors were not being achieved in 9% of cases. The authors concluded that most departments are achieving most vital organisational factors most of the time, but improvement is still possible. The results have been used as a basis for planning the organisation of public health departments in several of the newly formed commissioning agencies. This was the first regional audit of public health of its kind performed in the region and it provided valuable experience for planning future regional audit activity.